The role of sport psychology in injury prevention and rehabilitation in junior athletes - Weiß, M.; Büttner, M.; Richlan, F. (Behavioral Sciences, 2023)
Sports injuries have historically been addressed and treated from a purely physical perspective. Nevertheless, like in many other aspects of sports, it has become evident during the last decades that psychological considerations and consequent interventions are both vital and inevitable in the work with athletes, particularly in the work with junior athletes. Especially in the domains of sports injury prevention and rehabilitation, psychological measures can yield significant benefits for junior athletes. Stress management techniques, cognitive restructuring, mindfulness, motor imagery, or seeking social support have been demonstrated as being highly effective. These techniques, many of them originally intended by sport psychologists to optimize performance, now aid junior athletes in performing at their best while also preventing injury and facilitating a safe return to competition after injury. During injury rehabilitation, sport psychological measures play an important role as well. The purpose of this review is firstly to provide an overview of the psychological factors that significantly support both injury prevention and rehabilitation. We subsequently elaborate on the identification and optimization of these factors by presenting evidence-based psychological interventions and training programs. In addition, we provide science-informed fundamentals that may serve as a basis for the adaptation and/or development of novel psychological measures to support junior athletes during injury prevention and rehabilitation.